Future Prospects and Challenges of Hyperthermic Intraperitoneal Chemotherapy in Indonesia - Pratama, Muhamad Airel; Ihsan, Syarifaha; Linangkung, Arum (Indonesian Journal of Cancer, 2025)
Background: Peritoneal carcinomatosis (PC) is a condition characterized by the spread of cancer to the peritoneum, often indicating advanced disease and poor prognosis. Traditionally viewed as a terminal illness, PC typically shows limited response to systemic chemotherapy, prompting a shift towards local-regional management through cytoreductive surgery (CRS) followed by heated intraperitoneal chemotherapy (HIPEC). This study aims to evaluate the potential of introducing HIPEC as a treatment for PC in Indonesia.Methods: A Literature search was conducted in June 2024 by using PubMed as the main electronic database. General terms related to the search, such as “hyperthermic intraperitoneal chemotherapy OR HIPEC”, “peritoneal carcinomatosis OR PC”, “cancer”, and “Indonesia” were used in screening. We included clinical trials that focused on HIPEC for the treatment of PC, comprehensive review articles that discuss HIPEC and its application, as well as studies that provided cost analysis of implementing HIPEC. Two reviewers (MA and SI) were involved in screening and full-text reviews. A meeting was held daily to standardize the reviewers’ understanding. Discussion with one reviewer (AL) was done to analyze results and come up with a suitable discussion.Results: Numerous trials demonstrate the significant benefits of CRS and HIPEC for patients with PC of various origins. Several guidelines outline specific criteria for HIPEC eligibility to ensure optimal outcomes, while others consider the procedure as experimental. Despite its effectiveness, its high costs act as its main challenge, particularly regarding reimbursement policies. CRS-HIPEC, however, remains cost-effective when considering life-years gained compared to standard chemotherapy. Conclusions: While international studies have demonstrated the effectiveness of CRS-HIPEC in treating peritoneal carcinomatosis, the application of this treatment in Indonesia remains largely untested. This study highlights the need for further research on the feasibility, clinical outcomes, and infrastructure requirements for implementing HIPEC in Indonesia. To effectively implement HIPEC in Indonesia, it is essential to consider a few factors, including but not limited to reimbursement policies, adoption of eligibility guidelines, and establishing multidisciplinary standards.